Morbidity Patterns and Associated Factors among Elderly People: The Case of Sunkoshi Rural Municipality, Nepal - Thapa, Naba Raj; Rai, Mahendra Kumar (Humanities and Social Sciences Journal, 2022)
The rapidly increasing elderly population in Nepal is the most significant emerging demographic phenomenon. Multimorbidity is common among the elderly and its prevalence increases with age. This study aims to assess the chronic conditions and the demographic and socioeconomic factors that influence morbidity among the elderly. A cross-sectional study was carried out in the Sunkoshi rural municipality of Sindhuli district from December 2021 to January 2022 with 413 elderly people aged 60 and older using a structured questionnaire. Multinomial logistic regression was used for data analysis. About 27% of the elderly suffer from gastritis, followed by high blood pressure (27%), arthritis (24%), asthma (18%), and diabetes (10%). Seventy-seven percent of the elderly reported at least one morbidity and 41% have two or more morbidities. More than one-fifth of elderly people have no morbidity. In the multinominal logistic regression, moderate (RRR=3.31, 95% CI: 1.15-4.63) and poor (RRR=11.91, 95% CI: 1.00-141.83) self-reported health status was significantly associated with one morbidity. A joint family (RRR=2.01, 95% CI: 1.08-3.74), moderate (RRR=3.07, 95% CI: 1.52-6.21) or poor (RRR=32.05, 95% CI: 2.53-405.94) self-reported health status was significantly associated with two or more morbidity. Those aged 80 years or over, those who belonged to the hill Janajati, and those who consumed alcohol were less likely to have multimorbidity. Concerned authorities should consider expanding health services in order to improve the health status of the elderly.